2014
DOI: 10.4102/sajbm.v45i3.135
|View full text |Cite
|
Sign up to set email alerts
|

Customer orientation on new product activities and performance from the contract manufacturer’s viewpoint

Abstract: Studies have suggested the positive effect of customer orientation on superior performance. However, these studies have not shown how to covert customer orientation into superior performance through new product development (NPD) activities. The purpose of this study was to fill the gap between customer orientation and new product performance and elucidate the mediating influence of product launch, product development capability, and innovativeness on the relationship between customer orientation and new produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(86 reference statements)
1
0
0
Order By: Relevance
“…The finding regarding the relationship between customer orientation and NPD performance is in line with the majority of previous studies (e.g. Feng et al , 2012; Lee and Kou, 2014). Second, this research also found that TMS exhibits a moderating impact on CO-NPD relationships.…”
Section: Resultssupporting
confidence: 91%
“…The finding regarding the relationship between customer orientation and NPD performance is in line with the majority of previous studies (e.g. Feng et al , 2012; Lee and Kou, 2014). Second, this research also found that TMS exhibits a moderating impact on CO-NPD relationships.…”
Section: Resultssupporting
confidence: 91%